Determinan Yang Memengaruhi Sikap Mengenai Kekerasan Seksual Pada Remaja Di SMA Kosgoro Kota Bogor Tahun 2023 - Shanti Ariandini; Nina Yusnia; Sunarti Sunarti; Epa Parida; Zelitha Ayu; Iik Iklimah; Tria Amanda; Resti Ananda (Pusat Riset dan Inovasi Nasional, 2024)
Unwanted sex-related behavior, such as demands for sex and other physical and verbal sexual abuse, is known as sexual violence or harassment. These actions certainly have a significant and broad impact on people's lives, especially children and teenagers. The impact of sexual violence can last long after the experience ends and is closely related to the life circumstances of children and adolescents both during and after sexual interactions. Finding factors that influence the prevalence of sexual violence among adolescents is the aim of this research. In this study, 390 samples were randomly sampled using a cross-sectional strategy. Chi square was used in univariate and bivariate analysis. The analysis findings show that gender, age, knowledge, peers, and information media are the variables that have the strongest relationship with adolescent violence (p value <0.05). Sexual violence against teenagers is taught in schools, and as a preventive measure, local governments should expand their services for victims of sexual harassment.